Design and anti-sway performance testing of pesticide tanks in spraying UAVs - Zang, Yu; Zang, Ying; Zhou, Zhiyan; Gu, Xiuyan; Jiang, Rui; Kong, Lingxi; He, Xingang; Luo, Xiwen; Lan, Yubin (International Journal of Agricultural and Biological Engineering, 2019)
Anti-sway performance is one of the most important factors that affect the stability of unmanned aerial vehicles (UAVs). In this study, an anti-sway performance testing method and an evaluation formula for pesticide tanks were developed, which could facilitate the design and application of pesticide tank. The detection device mainly comprises a testing stand, a mounting and testing part, and a driving and control part. In the testing method, P (maximum pressure) measured by a barometer and t (fluctuation recovery time) measured by a high-speed camera were used as evaluation indexes. With the aim to determine the optimal position of the pressure detection device and the optimal filling ratio, four representative pesticide tanks were involved in this study. The results showed that the optimal position of the pressure detection device was at the middle position on the tank wall, halfway up from the bottom, and the optimal filling ratio was 0.8. Using P and t as evaluation indexes, a comprehensive evaluation formula was developed based on these tests: S=0.7Pi +0.3ti. Anti-sway performance of pesticide tanks was evaluated by a comprehensive score. A disk pesticide tank with a baffle was determined to be the best among the four types of pesticide tanks, showing a score of 1. The scores of the other three pesticide tanks were 0.500, 0.428 and 0.612, respectively. These results indicated that the baffle structure in the pesticide tank and the radian design of the tank wall can effectively improve the anti-sway performance of a pesticide tank. The proposed detection device and test method are simpler and more intuitive compared to other approaches in evaluating the anti-sway performance of pesticide tanks in spraying UAVs, and they can be used as a reference to guide the design of pesticide tanks and the stability evaluation of spraying UAVs. Keywords: spraying UAV, pesticide tank, liquid sloshing, anti-sway performance test, detection method DOI: 10.25165/j.ijabe.20191201.4338 Citation: Zang Y, Zang Y, Zhou Z Y, Gu X Y, Jiang R, Kong L X, et al. Design and anti-sway performance testing of pesticide tanks in spraying UAVs. Int J Agric & Biol Eng, 2019; 12(1): 10–16.